(untitled) (Journal of the Bangladesh Agricultural University, 2017)
With a view to assessing the effect of temperature (ºC) and locations on species richness of thrips and whiteflies and their natural enemies (NEs), predatory Geocoris bug and Asian lady bug beetle (LBB) in mustard field of BARI Sarisha 16, the experiment was carried out at the farmers fields in two specific locations of Southern Bangladesh, Rupsha, Khulna and Abhaynagar, Jessore during November, 2015 to March, 2016. The studies were laid out with randomized complete block deign (RCBD) maintaining four replicates. The results depicted that there was a significant variation in mean population abundance of thrips, whitefly and their predators across the observation dates, which principally resulted from the variation of temperature along the various observation dates in each location and between locations along with phenological characters of host plants. Initially, population of thrips and whitefly, and their predators were very low in both locations at first observation date of 20 November, 2015 which gradually colonized and reached the peak in 19 March, 2016 with temperature of 27.8°C and 71% RH in Khulna and 26.1ºC and 61% RH in Jessore. Notably, temperature ranging from 2227°C during mid-February to March, 2016 considerably favors the species richness of both insect pests, thrips and whiteflies, and their predators, Geocoris bug and Asian lady bug beetle in both places. By contrast relative low temperature of 1620°C from December 20, 2015 to January 29, 2016 affected the species richness of predators and pest as well. The yield of mustard, BARI Sarisha 16 was significantly higher in Jessore (1365.75 kgha1) due to lower pest population and higher predator population relative to Khulna region (1277.25 kgha1). Ecological factors especially temperature appeared as major striking factor of species richness and played crucial role in getting up and down of mustard insect pests and NEs population across various date of observations and between places. J. Bangladesh Agril. Univ. 15(1): 7-14, January 2017